COGNITIVE ANALYSIS OF LANDSCAPE TERMS IN UZBEK AND ENGLISH LANGUAGES (Scientific journal of the Fergana State University, 2024)
This article describes the cognitive issue of landscape terms in Uzbek and English languages. Also, the lexical units denoting certain individual water landscapes were studied as research objects, and the opinions expressed in Uzbek and English linguistics in this regard were studied as research objects. The cognitive mechanism of comparison consists in connecting concepts of objects or events in the mind on the basis of similar properties.